Effects of volume and composition of the resuscitative fluids in the treatment of hemorrhagic shock - Sharma, Pushpa (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: To evaluate the effectiveness of normal saline, hypertonic saline, and Ringer's lactate solution followed by blood infusion in ameliorating the physiological, biochemical, and organ functions following hemorrhagic shock (HS) in rats. MATERIALS AND METHODS: Anesthetized, male Sprague-Dawley rats underwent computer-controlled HS, and were randomly divided into five groups consisting of (1) sham, (2) HS without resuscitation, (3) resuscitation with normal saline, (4) resuscitation with hypertonic saline, and (5) resuscitation with Ringer's lactate solution. All resuscitated animals were infused with subsequent infusion of shed blood. Animals were continuously monitored for physiological, hemodynamic, biochemical parameters, and organ dysfunctions. RESULTS: Non-resuscitated animals were unable to survive due to hypotension, poor oxygen metabolism, and lactic acidosis. Although these HS related parameters were corrected by all the fluids used in this study, additional blood infusion was more effective than fluid resuscitation alone. Also, hypertonic saline was more effective than Ringer's lactate solution, and normal saline was the least effective in preserving the liver and kidney functions and muscle damage. CONCLUSIONS: All crystalloid fluids were significantly more effective in reversing the HS outcome when used with blood infusion, but hypertonic salinewith blood was more effective in preventing the organ damage than Lactated Ringers solutions or normal saline in the treatment of HS.